Peircean Semiotic Analysis of Cultural Identity in the Lepo Kirek Traditional House, Sikka Regency - Felisitas Siano; Desi Dwi Prianti (MASI Mandiri Edukasi, 2026)
The Lepo Kirek traditional house in Hewokloang, Sikka Regency, Indonesia, represents a significant expression of cultural identity that is increasingly challenged by modernization. This study aims to analyze how architectural elements of the Lepo Kirek traditional house represent and sustain cultural identity through Charles Sanders Peirce’s semiotic framework, focusing on icon, index, and symbol. This research employs an interpretive ethnographic approach. Data were collected through participatory observation, visual analysis, and image-based interviews with four informants, including customary leaders, cultural observers, and community members. The fieldwork was conducted over a period of one month, allowing in-depth engagement with cultural practices and architectural meanings. The findings reveal that the Lepo Kirek traditional house operates as a dynamic semiotic system. First, the roof form of Buwun Sikon Sakok Manu Ladon functions as an icon representing protection and ancestral strength. Second, spatial structures such as Ulu Higun (sacred space) and Pekang Gete (communal space), along with ritual practices and material selection, serve as indices of the relational system among humans, ancestors, and nature. Third, carvings, ritual objects, and the concept of the house as a “microcosm” function as symbols constructed through collective cultural conventions. Additionally, the study identifies ongoing reinterpretation through material adaptation and the integration of religious elements without eliminating core cultural meanings. This study concludes that the Lepo Kirek traditional house is a living cultural text that continuously negotiates identity. The research contributes theoretically by integrating Peircean semiotics with ethnographic context in analyzing traditional architecture, and practically by providing insights for cultural preservation strategies in the context of modernization.